Formation of biogenic amines in the cheese production chain: Favouring and hindering factors. (October 2022) - Schirone, Maria; Visciano, Pierina; Conte, Francesca; Paparella, Antonello
Abstract: The presence of biogenic amines in cheeses is due to microbial enzymes showing decarboxylation or amination activity. They are generally low in raw milk, while in fermented or ripened cheeses and dairy products much higher concentrations can be found. This review focuses on the main factors associated with the raw material as well as the different technological processes affecting biogenic amine formation in these foods. Some innovative strategies are also described as important preventive measures to be recommended to operators engaged in the dairy sector.